Acute respiratory failure after aspiration of activated charcoal with recurrent deposition and release from an intrapulmonary cavern - Francis, Roland C. E.; Schefold, Joerg C.; Bercker, Sven; Temmesfeld-Wollbrueck, Bettina; Weichert, Wilko; Spies, Claudia D.; Weber-Carstens, Steffen (Intensive Care Medicine, 2009)
Objective: To report on the recurrent release of charcoal from an intrapulmonary cavern in a case of acute respiratory failure after charcoal aspiration. Design: Case report. Setting: Anaesthesiological ICU, university hospital. Patient: An 18-year-old ethanol intoxicated comatose patient regurgitated and aspirated activated charcoal during orotracheal intubation. Treatment: After 2 days of mechanical ventilation, the patient was transferred to a tertiary care university hospital. On admission, acute respiratory distress syndrome with bilateral pulmonary infiltrations was diagnosed. The patient's recovery was hampered by recurrent release of charcoal from an intrapulmonary cavern. Sophisticated ventilatory support, prone positioning, secretolytics, repetitive bronchoscopy, and antibiotic therapy may have facilitated bronchoalveolar clearance and weaning after 18 days. Conclusion: Aspiration may be a dramatic complication if charcoal is administered in comatose patients without airway protection. In this case report, advanced intensive care measures were necessary to tackle the special feature of charcoal release from an intrapulmonary cavern. © 2008 Springer-Verlag.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Activated charcoal; Acute respiratory distress syndrome; Acute respiratory failure; Aspiration; Cavern